The effects of sukuk characteristics towards issuer’s market valuation / Noriza Mohd Saad and Dr. Mohd Nizal Haniff - Abdol Ghapar, Dr Hjh Farha; Ismail, Mazida; Mohd Ramsi, Mohd Faizal; Md Nawi, Sofwah; Hassan, Suzana; Suhaimi, Azrina (2013)
Purpose – This main objective of the study is to investigate the impact of sukuk characteristics towards issuer’s market valuation as regards to tenure, RAS rating and size of issuance in Malaysian Sukuk Market.